A conceptual foundation for blockchain development: the contribution of Ibn Khaldun - Hassan, Rusni; Mohammad, Burhan Uddin; Hossain, MD Alamgir; Hasan, MD Tareq (UUM Press, 2021)
Blockchain is a game-changing technology that has the ability to solve plenty of real-world issues in the digital age. Blockchain is a subject of huge interest in many industries and academia in terms of discovering technology and classifying challenges and innovative practical application for the industry. This study addresses the challenges that are of main concern in designing a Blockchain platform. In this regard, the problems such as privacy, regulation, security, lack of adequate skill sets, energy consumption, inefficient technology design, the criminal connection, scalability, energy consumption, and public view are discovered to be important. Due to such challenges, the blockchain technologies have emitted a negative impression due to its incapability to be successfully applied while, at the same time, its benefits could not be fully gained by its investors. The objective of this study, hence, is to assess the blockchain advantages and growth in light of the eight foundations for economic development as advocated by Ibn Khaldun. Expending Ibn Khaldun’s philosophy, each challenge is deliberated and investigated to find the answers and solutions for addressing and overcoming the afore-mentioned challenges.